On the convergence on the Grassmannian - Villavicencio, Helmuth (2020)
In this paper, we present a characterization of the convergence on the n-th order Grassmannian that permits us to show in a direct way that this set is compact and every vector bundle is measurable. Finally, we obtain a criterion to induce measurable bundles.